Street vending: exploring an excluded economic sector in Chittagong city, Bangladesh. Issue 3 (3rd April 2021) - Uddin, M. Ala
ABSTRACT: As an informal economic activity, street vending has become an urban phenomenon both in developing and developed countries. This article uses an empirical study to explore the lives, livelihoods, and challenges of street vendors in Chittagong city. It finds that street vending is a viable employment source, meeting most people's daily needs. However, owing to lack of recognition, necessary facilities, and support, vendors often run their business with risk and uncertainty. The article recommends the inclusion of street-vending businesses into urban planning and economy to improve their lives, business, and city ecology.